Pentacyclic adenine: a versatile and exceptionally bright fluorescent DNA base analogue. Issue 14 (9th March 2018) - Bood, Mattias; Füchtbauer, Anders F.; Wranne, Moa S.; Ro, Jong Jin; Sarangamath, Sangamesh; El-Sagheer, Afaf H.; Rupert, Déborah L. M.; Fisher, Rachel S.; Magennis, Steven W.; Jones, Anita C.; Höök, Fredrik; Brown, Tom; et al.
Abstract : A highly fluorescent, non-perturbing, pentacyclic adenine analog was designed, synthesized, incorporated into DNA and photophysical evaluated. Abstract : Emissive base analogs are powerful tools for probing nucleic acids at the molecular level. Herein we describe the development and thorough characterization of pentacyclic adenine (pA), a versatile base analog with exceptional fluorescence properties. When incorporated into DNA, pA pairs selectively with thymine without perturbing the B-form structure and is among the brightest nucleobase analogs reported so far. Together with the recently established base analog acceptor qAnitro, pA allows accurate distance and orientation determination via Förster resonance energy transfer (FRET) measurements. The high brightness at emission wavelengths above 400 nm also makes it suitable for fluorescence microscopy, as demonstrated by imaging of single liposomal constructs coated with cholesterol-anchored pA–dsDNA, using total internal reflection fluorescence microscopy. Finally, pA is also highly promising for two-photon excitation at 780 nm, with a brightness (5.3 GM) that is unprecedented for a base analog.